Acoustic Parameters of Normal Voice - Vanaja C.S (Journal of All India Institute of Speech and Hearing, 1970)
Within recent years, speech science has focussed on changes in pa ienV speech that accompany laryngeal pathology. Researchers have tried to show that voice of patients carry sufficient information for differentiating various laryngeal pathologies.